2017
DOI: 10.29252/jea.4.7.30
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the Effective Factors on the Development of Agricultural Entrepreneurship in Rural Development (Case Study of Kouhestan District, Rostamkola City)

Abstract: Entrepreneurs are the engines of economic development and have a special place in agricultural development and especially in rural development. For this reason, one of the most important strategies that have been used by many countries in recent decades to develop rural areas is the development of agricultural entrepreneurship. Therefore, the aim of this study was to investigate and prioritize the factors affecting the development of agricultural entrepreneurship in rural areas of Rostamkola. The library and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The research also looks at entrepreneurial programs and their effects on both women and young farmers. Research has also found, however, that entrepreneurship in the agricultural sector can affect economic and rural development with social factors influencing entrepreneurship the most [10]. It should be noted that there is a lack of studies on entrepreneurship in the agricultural industry in the developed world and in the Ag Tech sector.…”
Section: Entrepreneurshipmentioning
confidence: 99%
“…The research also looks at entrepreneurial programs and their effects on both women and young farmers. Research has also found, however, that entrepreneurship in the agricultural sector can affect economic and rural development with social factors influencing entrepreneurship the most [10]. It should be noted that there is a lack of studies on entrepreneurship in the agricultural industry in the developed world and in the Ag Tech sector.…”
Section: Entrepreneurshipmentioning
confidence: 99%